(3efgd GddWGFa aj GdcfGaI hGdbWGjas - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg gPG LRA SejJg efgd GddWGFa ai GdcfGaI hGdbWGja s
(3BNQgG (B:s
(3cCfgG bhd GHf eYW GdfMhi YOJgG Cda NdJ ef MTh s
(3Vef eLehY , JQJjHgG (B: (3ef U (B93 (3X (B- (3U(B100 (3Xs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B118 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjJhfg (B((3GdCMeOjg(B) - (3JhfS (B(4763) s
Keywords: (3GdCOHs